Advances in Relationship Between Alcohol Consumption and Skin Diseases - Liu L; Chen J (Clinical, Cosmetic and Investigational Dermatology, 2023)
Lin Liu, Jin Chen Department of Dermatology, The First Affiliated Hospital of Chongqing Medical University, Chongqing, People’s Republic of ChinaCorrespondence: Jin Chen, Department of Dermatology, The First Affiliated Hospital of Chongqing Medical University, No. 1 Youyi Road, Yuzhong District, Chongqing, 400016, People’s Republic of China, Tel +86 15023188592, Email chenjin19771010@163.comAbstract: Throughout history, alcohol consumption has been an integral part of human culture. Alcohol consumption, alcoholism in particular, influences the onset and progression of liver diseases, neurological disorders, and multiple types of cancer. However, the role of alcohol consumption in influencing skin diseases has often been overlooked. In this review, we present the progress of research investigating the effects and potential mechanisms of action of alcohol consumption on acne, rosacea, psoriasis, atopic dermatitis, melanoma, and non-melanoma skin cancer.Keywords: ethanol, acne, rosacea, psoriasis, atopic dermatitis, skin tumor